DIMENSI KEKUASAAN PENGHULU ADAT MELAYU RIAU DALAM PELAKSANAAN DEMOKRASI LOKAL - Asrinaldi Asrinaldi; Azwar Azwar (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2018)
The Malay penghulu adat have traditional authority that can direct their people to maintain their own identity and existence. In fact, although the function of these Malay penghulu adat is only in the context of customs and culture, but in some cases these penghulu also influence the implementation of local democracy.  For example, in the election process of the head of the region, although the function of the penghulu adat leader as a leader can direct the tribe and his people, but this function is rarely used because it is contrary to the principle of propriety in Malay custom. Nevertheless, the presence of this penghulu adat remains important to strengthen the legitimacy of the power of the political elite.  This is reasonable because the legitimacy of the Malay customary is very important as a basis for building political support derived from indigenous communities. This article is derived from field research using descriptive qualitative methods. The informants of this research are adat penghulu, members of local elections commissions, bureaucrats, politicians and local academics. This article finds the dimensions of  the Malay penghulu adat authority only used to establish Malay identity by strengthening Malay customs and culture. Moreover, the people of Riau are more complex than the social and cultural aspects. Their involvement gives support to the regional head only in order to preserve Malay culture to be accommodated in local government policy and not in the form of political activity. Therefore it is not surprising that every Riau governor is given the title of Datuk Seri Setia Amanah customs so that those who are given this title take part in preserving Riau Malay culture.